Low-intensity muscle contraction exercise following the onset of arthritis improves hyperalgesia via reduction of joint inflammation and central sensitization in the spinal cord in a rat model. (27th July 2019) - Ishikawa, Kumiko; Kajiwara, Yasuhiro; Sakamoto, Junya; Sasaki, Ryo; Goto, Kyo; Honda, Yuichiro; Kataoka, Hideki; Okita, Minoru
Highlights: Low-intensity muscle contraction exercise during the acute phase of arthritis reduced primary and secondary hyperalgesia. Exercise may ameliorate of the arthritis followed by inhibition of central sensitization in the spinal cord. Transcutaneous electrical nerve stimulation may reduce only primary hyperalgesia through reduction of central sensitization. Abstract: We examined the effect of immobilization, low-intensity muscle contraction exercise, and transcutaneous electrical nerve stimulation (TENS) on tissue inflammation and acute pain following the onset of arthritis in a rat model. Sixty Wistar rats were divided into five groups: (1) Arthritis group, (2) arthritis and immobilization (Immobilization group), (3) arthritis and low intensity muscle contraction (Exercise group), (4) arthritis and TENS (TENS group), and (5) sham arthritis (Sham group). Arthritis was induced in the right knee joints by single injection of 3% kaolin and carrageenan. Immobilization of the right hindlimb was conducted by full extension of the right knee joints and full plantar flexion of the ankle joints using a plaster cast for 7 days after injection. The right quadriceps muscles were subjected to electrical stimulation (frequency: 50 Hz; intensity: 2–3 mA) for 20 min/day as contraction exercise for one week. TENS was delivered at 20 min/day for one week (frequency: 50 Hz; intensity: 1 mA). The pressure pain threshold (PPT) and paw withdrawal response (PWR) were evaluated at 1 and 7 days after injection. We also analyzed the number of CD68-positive cells in the synovium by immunohistochemistry and determined the expression level of calcitonin gene-related peptide (CGRP) in the spinal dorsal horn with immunofluorescence. Improvements of both PPT and PWR were observed in the Exercise group at 7 days after injection compared to those of the Arthritis and Immobilization groups, although only improvement of PPT was observed in the TENS group. The number of CD68-positive cells in the synovium and CGRP expression in the dorsal horn decreased only in the Exercise group. These results suggested that low-intensity muscle contraction exercise might be a better treatment for reduction of arthritis-induced inflammation and acute pain compared to immobilization and TENS.